Analisis Marka RAPD yang Terpaut dengan Toleransi terhadap Naungan pada Kedelai - Desta Wirnas; Didy Sopandie; , Trikoesoemaningtyas; , Sobir (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The objective of the research was to identify RAPD markers linked to QTL related to agronomic traits of soybean under low-light intensity condition. The genetic material used in the QTL analysis based on RAPD Markers were Ceneng, Godek, and F6 RILs derived from hybridization between Ceneng (tolerant parent) and Godek (sensitve parent). The results of molecular analysis showed that 9 primers were polymorphic and linked to the tolerant parent. Primers produce 14 RAPD markers which were polymorphic and linked to the tolerant parent. The markers were distributed into a linkage group that containing seven markers. RAPD Markers (OPE15-800, OPM20-800) were linked to two QTL controlling number of productive node and seed weight, respectively. The marker linked to the tolerant parent could be used as a marker assisted selection for high-yielding soybean lines under low-light intensity